PENGANTIN PESANAN DARI INDONESIA KE CINA: Perdagangan Manusia Modern (UNTOC & PROTOCOL 2000) - Razita Aina Putri (2022)
In this study will examined the issue of human trafficking from Southeast Asia countries to China. The majority of human trafficking victims are poverty women and children seeking a better life. Human trafficking, as mentioned in this study, is a type of enslavement that comes in the form of marriage from Indonesia to China. This began when China was recognized as a source, transit, and destination country for human trafficking. However, the problem is escalating since UNTOC and Protocol 2000, the basis of international law that particularly regulates trafficking in persons, do not consider marriage as a type of enslavement practice. This has an effect on Chinese domestic legislation, resulting in gaps and loopholes in the incidence of custom brides. Although the form of bride purchase is not specified in the Protocol 2000, it is noted that all kinds of slavery can be classified as human trafficking. Therefore, this study also addresses how the governments of the Republic of Indonesia and China have made significant action to prevent bride trafficking, such as providing assistance and legal protection to victims. The victims' successful repatriation is the outcome of strong cooperation between the Indonesian and Chinese governments. Foreign Minister Retno Marsudi met with Chinese State Counselor Wang Yi in a bilateral meeting. The Indonesian Foreign Minister proposed facilitating the victims' repatriation. She also advocated collaborative efforts against human trafficking as a sort of prevention strategies. The author's research method in this study is normative juridical with a statutory approach. keyword : untoc&protocol 2000, human trafficking, bride trafficking indonesia&china